The impact of internal marketing upon an employees’ commitment in the organization. / Sharifah Insyirah Said Ismail - Said Ismail, Sharifah Insyirah (Faculty of Business and Management, 2017)
Employees’ commitment is described as the strength of an employees’ attachment to the organization. It is important in having a very good commitment from employees’ to achieve corporate objectives and staying long in the organization. This thesis is conducted to investigate the relationship between six factors which are communication, staff development, information and communication of technology (ICT), fairness, empowerment and teamwork with employees’ commitment in the organization. This is because there was no latest research study conducted to analyze the impact of internal marketing towards employees’ commitment in the organization. Researches from previous study on employees’ commitment have stated that six independent variables that are related with employees’ commitment were communication, staff development, information and communication of technology (ICT), fairness, empowerment and teamwork. The objective of the research study was to investigate the relationship between six factors which are communication, staff development, information and communication of technology (ICT), fairness, empowerment and teamwork with employees’ commitment in the organization. Besides that, this research also tends to investigate the impact of internal marketing on employees’ commitment in the organization. This research entitled “The Impact Of Internal Marketing Among Employees of Utusan Melayu (Malaysia) Bhd Upon An Employees’ Commitment In The Organization”. Research study had been conducted to obtain results and findings. There was a list of 291 respondents that were involved in answering the questionnaires that had distributed to them. There were available sources data from previous research had been used as references to understand the issues or matters arise in the research study. This research concludes with discussion on the results, study limitation and recommendation for future research.